Evening [videorecording (DVD)] - Koltai, Lajos; Danes, Claire, 1979-; Collette, Toni; Redgrave, Vanessa, 1937-; Minot, Susan (Universal Studios Home Entertainment, 2007)
Overcome by the power of memory, Ann Lord reveals a long-held secret to her concerned daughters. Constance is a content wife and mother. Nina is a restless single woman. Both are bedside when Ann calls out for the man she loved more than any other. But her daughters wonder who is Harris and what is his relation to their mother? Constance and Nina try to take stock of Ann's life as their mother is tended to by a night nurse as she journeys into her mind back to a summer weekend some fifty years before, before she was married, going from New York City to be maid of honor at the high-society Newport wedding of her dearest friend from college, Lila Wittenborn. The bride-to-be is jittery, and turns to her maid of honor rather than her own mother for support. Ann stays close to her friend, yet is even closer to Lila's irrepressible brother Buddy. Unexpected feelings surge forth once Ann meets wedding guest Harris Arden, a lifelong friend and intimate of the Wittenborn family. Ann's love for Harris will change her life, and those of her daughters, forever.